Variation throughout the tree stem in the physical-mechanical properties of the wood of Abies alba Mill. from the Spanish Pyrenees - González-Rodrigo, Beatriz; Esteban, Luis G.; Palacios, Paloma; García-Fernández, Francisco; Guindeo, Antonio (Instituto de Ecología, A.C., 2013)
This study analyses the variation of main physical-mechanical properties of wood along the longitudinaland radial directions of the tree for Abies alba Mill. growing in the Spanish Pyrenees. Smallclear specimens were used to study the properties of volumetric shrinkage (VS), density (ρ), hardness(H), bending strength (MOR), modulus of elasticity (MOE), maximum compressive strength parallel tothe grain (MCS) and impact strength (K). Several models of properties variation in the longitudinal andradial directions were analyzed. Main trends of variation of properties throughout the tree stem wereidentified although none of them could be fitted to predictive statistical models. Along the longitudinaldirection, the properties studied followed a downward trend from the base to the crown, which was notsignificant in all cases, indicating that no differences in quality existed. Throughout the radial directionthe trend is upward for the first 40-50 growth rings, after which it slopes downwards, more gently at firstuntil rings 70-75 and then more steeply. This behaviour is related to variation in wood structure from thepith to the bark, depending on whether the wood is juvenile, sapwood or heartwood, and to wood maturityand microfibril angle. Authors encourage carrying further studies on other populations of A. alba inthe Spanish Pyrenees to check if the trends found in this study apply to other provenances.